Analisis kualitas search engine sebagai media pembelajaran online di perpustakaan perguruan tinggi di Bali - I Putu Suhartika; Ni Putu Premierita Haryanti (Perpustakaan Universitas Gadjah Mada, 2022)
Introduction. Previous research on the quality of search engines through a combination of three supporting theories is limited. This research which used the three theories aims to measure the quality of search engines based on user perceptions, utilization, and recall and precision values. The three supporting theories include recall and precision analysis, TAM (Technology Acceptance Model) and WebQual. Research methods. This study used a quantitative inferential method with questionnaires, observations, and online search. Data analysis. This study used inferential statistical data analysis techniques which used to determine the relationships among research variables. Results and discussion. Search engine Yahoo shows the highest recall value, while Google shows the highest precision value. The two search engine are well accepted and used frequently by users. The usability quality dimension has a significant effect on the utilization of Google and Yahoo, while the interaction quality dimension has no significant effect on those two search engines. Meanwhile, the dimension of information quality has a significant effect on Yahoo, however, it has no a significant effect on Google. Conclusion and suggestions. The two search engines are accepted by user. They used as online learning media in universities to provide ease of use and support user interaction.